SHARIA CREDIT RISKS: WOMEN'S ROLE IN REDUCING POVERTY - Lesmana, Ceta Indra (PT. Altin Riset Publishing, 2024)
Alleviation poverty, especially among women, is a serious challenge in Indonesia. Finance microsharia emerged as a potential solution. For empowerment, women should approach sharia credit. This article discusses necessary risks noticed, like credit traffic jams, fraud, and risk reputation, in development finance microsharia. Management good risk has become a key continuity business. Apart from that, the importance of education and literacy finance, supporting the government, and partnerships with various parties in increasing the contribution of women to overcome poverty through Sharia credit is highlighted. Utilisation of the potential for zakat, waqf, and Islamic values is also a crucial aspect. Inclusionary and sustainable microfinance models are expected to positively impact women's economic empowerment. With a holistic, inclusive, and sustainable approach, it is hoped that women can play a significant role in alleviating poverty and positively impacting various layers of society in Indonesia.